Η αξιοποίηση των σχολικών βιβλίων στην εκπόνηση δημιουργικών εργασιών στο Ενιαίο Λύ-κειο - Μανωλάς, Ευάγγελος Ι.; Θεοδωρόπουλος, Ιωάννης Ε. (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
This paper, after a brief presentation of the legal framework regarding the writing of creative essays in the unified upper secondary school, (1) identifies and analyzes some reasons for the use of school textbooks as sources for creative essays and (2) reveals some elements from textbooks used in the last year of studies in the unified upper secondary school, which can be exploited by the student in the writing of creative essays. In particular, the suggestions put forward in this paper for the writing of creative essays, as these emerge from specific textbooks, reflect the progress which has been made in recent years regarding the upgrading of the quality of school textbooks but, at the same time, they call for new and productive ways in which these books can be used.